NiCoSe4 nanoparticles derived from nickel–cobalt Prussian blue analogues on N-doped reduced graphene oxide for high-performance asymmetric supercapacitors. (20th August 2022) - Yang, Quanlu; Feng, Qiaoliang; Xu, Xin; Liu, Yang; Yang, Xuexue; Yang, Fawang; Li, Jiankun; Zhan, Huiying; Wang, Qianshan; Wu, Shang
Abstract: Synthesis of NiHCCo precursors via simple co-precipitation and nickel–cobalt tetraselenide composites grown on nitrogen-doped reduced graphene oxide (NiCoSe4 /N-rGO) were fabricated using solvothermal method. The introduction of N-rGO used as a template effectively prevented agglomeration of NiCoSe4 nanoparticles and provided more active sites, which greatly increased the electrochemical and electrical conductivity for NiCoSe4 /N-rGO. NiCoSe4 /N-rGO-20 presents a remarkably elevated specific capacity of 120 mA h g −1 under current density of 1 A g −1 . NiCoSe4 /N-rGO-20 demonstrates an excellent cycle life and achieves a remarkable 83% retention rate over 3000 cycles with 10 A g −1 . NiCoSe4 /N-rGO-20//N-rGO asymmetric supercapacitor was constructed based on the NiCoSe4 /N-rGO-20 as an anode, N-rGO as cathode by using 2 mol l −1 KOH as an electrolyte. NiCoSe4 /N-rGO-20//N-rGO ASC demonstrates an ultra-big energy density of 14 Wh kg −1 and good circulation stability in the power density of 902 W kg −1 . It is doubled in comparison to the NiCoSe4 /N-rGO-20//rGO asymmetric supercapacitor (7 Wh kg −1 ). The NiCoSe4 /N-rGO-20//N-rGO ASC capacity retention is still up to 93% over 5000 cycles (5 A g −1 ). The results reveal that this device would be a prospective cathode material of supercapacitors in actual applications.